Cross-Market Heding during The Credit Crunch - Huang, Yibing (2008)
Systematic risks cannot be eliminated by diversifying within one market. However, the systematic risk of the combined markets can be reduced significantly by hedging across the markets. It is an alternative way to hedge against the systematic risk apart from holding particular futures contracts. This research employs samples from FX and equity markets to prove the hedging possibility. Empirical results, especially of samples during the latest credit crunch period, support the assumptions satisfactorily and the hedging against the systematic risk is applicable when this sort of risk becomes outstanding. Nevertheless, this paper suggests that not any two markets have preconditions for hedging but they can be selected primarily by reviewing their economic properties and other interconnections. Moreover, evidences of solidly correlated period and existence of risk-reducing features in these periods are needed to be found.